POTRET ISLAM SEBAGAI AGAMA DAN PERADABAN MODERN - Fauzi Fahmi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Islam is actually more than just a religion but a perfect civilization. Islam teaches how to form a culture and the process towards further shaping civilization in the development of human life. This research uses the literature study method that relies on bibliographical sources from books and articles in scientific journals. The results of this study show, among others: 1) The influence of Islam as a religion that has a concept of rules so that it must be implemented in human life to achieve a perfect civilization. 2) The development factor of a civilization a) Islamic view of life as a foundation for building Islamic civilization, b) The development of science, c) Social and political stability. Then some of the factors for the decline of a civilization a) Injustice and injustice, b) Division and strife, c) Moral depravity.